ELECTRONIC CONDUCTION PHENOMENA OBSERVED ON THE SURFACE OF SEMICONDUCTORS AND METALS (Scientific journal of the Fergana State University, 2024)
This article analyzes the phenomenon of electronic conductivity observed on the surface of semiconductors and metals. With the development of electronics at the end of the 20th century, the movement of electrons in metals and semiconductors and their distribution in the electrical field were explained in terms of statistical balance. The propagration processes of electrons slow down their acceleration, resulting in electrical resistance. It has also been found that electrical conductivity of thin layers and wires is significantly lower compared to mass samples. At JJ Thomson's suggestion, this great effect may be explained by the additional surface spread.